The Forex Regime and EMU Expansion - Pieter W. van Foreest; Casper G. de Vries (Tinbergen Institute, 2002)
This paper provides evidence that the choice of the foreign exchange regime is not of first order importance for achieving high output growth. It is argued that due to the forward looking nature of the foreign exchange market, exchange rate stability hinges on the current and anticipated coherency of monetary and fiscal policies. We demonstrate this empirically on a panel including potential EMU accession countries. By means of rank regression analysis we uncover the partial links across the regime specifics of the representative country versus the German regime during the 1990s.
Keywords: 330; Exchange Rate Regime; Growth; EMU; CEECs; Wechselkurssystem; Wirtschaftswachstum; Monetäre Wechselkurstheorie; Eurozone; Übergangswirtschaft; EU-Staaten; Osteuropa